1995
DOI: 10.1172/jci118085
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action on heart and skeletal muscle glucose uptake in essential hypertension.

Abstract: Essential hypertension is characterized by skeletal muscle insulin resistance but it is unknown whether insulin resistance also affects heart glucose uptake. We quantitated whole body (euglycemic insulin clamp) and heart and skeletal muscle (positron emission tomography and 18F-fluoro-2-deoxy-D-glucose) glucose uptake rates in 10 mild essential hypertensive (age 33±1 yr, body mass index 23.7±0.8 kg/ mI, blood pressure 146±3/97±3 mmHg, Vo2, v 37±3 ml/ kg per min) and 14 normal subjects (29±2 yr, 22.5±0.5 kg/M2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 43 publications
5
54
1
Order By: Relevance
“…In contrast, in athletes with a decrease in cardiac work per heart mass, insulin-stimulated glucose uptake in the heart is diminished, while peripheral insulin sensitivity is enhanced [14]. In patients with essential hypertension, the opposite picture emerges: heart glucose uptake and cardiac work per unit heart mass are increased in proportion to the elevation of blood pressure, while peripheral insulin sensitivity is decreased [25]. Thus, if changes in insulin sensitivity are associated with alterations in cardiac work (hypertension, physical fitness), heart glucose uptake is altered in proportion to the altera- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in athletes with a decrease in cardiac work per heart mass, insulin-stimulated glucose uptake in the heart is diminished, while peripheral insulin sensitivity is enhanced [14]. In patients with essential hypertension, the opposite picture emerges: heart glucose uptake and cardiac work per unit heart mass are increased in proportion to the elevation of blood pressure, while peripheral insulin sensitivity is decreased [25]. Thus, if changes in insulin sensitivity are associated with alterations in cardiac work (hypertension, physical fitness), heart glucose uptake is altered in proportion to the altera- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other data imply that myocardial insulin resistance does not always parallel skeletal muscle insulin resistance. For example, MGU was reported to be increased in essential hypertension while SMGU and the whole body glucose disposal rate were significantly reduced in the same study patients [9]. Furthermore, Yokoyama et al also reported that MGU was similar in both hypertensive T2DM and controls despite significantly reduced SMGU and whole body glucose disposal rates in the former indicating an existence of insulin resisatnce in skeletal muscle and whole body but not in the heart in patients with T2DM and hypertension [18].…”
Section: Main Part Of Review and Discussionmentioning
confidence: 81%
“…Reduced SMGU during insulin clamping, implying insulin resistance in the skeletal muscle, has been reported in patients with type-2 diabetes (T2DM) [7,8], patients with hypertension [9] and patients with non-diabetic non-hypertensive hypertriglyceridemia [10] using quantitative PET and 18 F-FDG and and hyperinsulinemic euglycemic glucose clamp technique. Reduced SMGU and linear positive relationship between SMGU and whole body glucose disposal rate during insulin claming was also shown in patients with T2DM, non-diabetic hypertension and non-diabetic non-hypertensive hypertriglyceridemia with similar magnitude [11].…”
Section: Main Part Of Review and Discussionmentioning
confidence: 99%
“…Recently, positron emission tomography (PET) has emerged as a technique to allow in vivo quantitative analysis of tissue metabolism. This has made it possible to quantify glucose metabolism in skeletal muscle [16][17][18][19] by 18 FDG PET. As a result, reduced SMGU in patients with T2DM [19] and in patients with mild hypertension [18] has been documented.…”
Section: Introductionmentioning
confidence: 99%
“…This has made it possible to quantify glucose metabolism in skeletal muscle [16][17][18][19] by 18 FDG PET. As a result, reduced SMGU in patients with T2DM [19] and in patients with mild hypertension [18] has been documented. However, it has not been clarified whether whole body insulin resistance and SMGU, or the relationship between SMGU and GDR, differ among subjects at high risk for CAD.…”
Section: Introductionmentioning
confidence: 99%